Living Qur'an in the Tradition of Rejecting Bala: The Role of Qur'anic Verses in Miftahul Falah Qur'anic Tahfizul Boarding School - Nida, Sofwatun; Mandar, Yasri; Krismonadi, Fani; Hidayah, Ahwil Lutan; Hidayat, Yusron (Jurnal Studi Sosial Keagamaan Syekh Nurjati, 2025)
Abstract: Purpose- This study aims to explore the role of Qur'anic verses in the Ritual of Tolak Bala at Pondok Pesantren Tahfizul Quran Miftahul Falah Cirebon, focusing on how these verses are practiced and understood within the ritual. Design/methods/approach- The research employs a qualitative methodology with a descriptive approach. Primary data were collected through interviews with pesantren caregivers, teachers, students, and local community members, while secondary sources were obtained from journal articles, books, classical Islamic texts (kitab kuning), and documentation. Findings- The findings indicate that specific Qur'anic verses—particularly Ayat Kursi and selected chapters—hold a central spiritual function in the implementation of the Tolak Bala ritual. This ritual serves as a means of invoking divine protection and reflects both a functional interpretation of the Qur'an and the continuity of the living Qur'an tradition within the pesantren environment. Research Implications- This study highlights the enduring relevance of local religious practices rooted in Qur'anic spirituality. It emphasizes the importance of contextualizing Islamic traditions within communal rituals, ensuring that such practices continue to thrive as expressions of faith and cultural identity in contemporary pesantren life.